GAMBARAN KEPATUHAN PENGGUNAAN MASKER PADA MASYARAKAT DI MASA PANDEMI DI KECAMATAN KOTA TENGAH - Susanti Monoarfa; Pipin Yunus; Nur Oktaviani A. Datau; Desi I. Yantiko (Jurnal Rumpun Ilmu Kesehatan, 2021)
The use of masks during the Covid-19 pandemic is very important to protect yourself and others from the risk of transmitting this virus. As it is known that most of the transmission of Covid-19 is through droplets, it is felt necessary to protect yourself. Masks can be a barrier for droplets both coming from within and from others. The purpose of research was to determine the description of compliance with the use of masks in the community during the pandemic in Kota Tengah District. This research method uses a quantitative descriptive approach with a cross sectional design. Samples were taken using cluster random sampling technique, Data was collected using a questionnaire sheet and data analysis was carried out using a frequency distribution table. The results showed that most of the people of Kota Tengah district were obedient in using masks but there were still many who did not comply with using masks